2018
DOI: 10.1111/apha.13208
|View full text |Cite|
|
Sign up to set email alerts
|

High‐intensity exercise training ameliorates aberrant expression of markers of mitochondrial turnover but not oxidative damage in skeletal muscle of men with essential hypertension

Abstract: Aim: To examine whether hypertensive individuals exhibit altered muscle mitochondrial turnover and redox homeostasis compared with healthy normotensive counterparts, and whether the antihypertensive effect of high-intensity exercise training is associated with improved mitochondrial quality and enhanced anti-oxidant defence. Methods: In a cross-sectional and longitudinal parallel design, 24 essential hypertensive (HYP) and 13 healthy normotensive (NORM) men completed 6 weeks of high-intensity interval training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 88 publications
1
33
3
Order By: Relevance
“…It is notable that the hypertensive group did not improve theirVO 2 -max during the training intervention, which is in contrast to the normotensive group and to previous observations in similar patient groups implementing 10-20-30 cycling training (Fiorenza et al, 2019;Gunnarsson et al, 2020). ThatVO 2 -max did not improve with training in the hypertensive individuals of the present study is not easily explained as 7-8 weeks of 10-20-30 training improved thė VO 2 -max in trained runners (Gunnarsson and Bangsbo, 2012;Gliemann et al, 2015).…”
Section: Discussioncontrasting
confidence: 82%
“…It is notable that the hypertensive group did not improve theirVO 2 -max during the training intervention, which is in contrast to the normotensive group and to previous observations in similar patient groups implementing 10-20-30 cycling training (Fiorenza et al, 2019;Gunnarsson et al, 2020). ThatVO 2 -max did not improve with training in the hypertensive individuals of the present study is not easily explained as 7-8 weeks of 10-20-30 training improved thė VO 2 -max in trained runners (Gunnarsson and Bangsbo, 2012;Gliemann et al, 2015).…”
Section: Discussioncontrasting
confidence: 82%
“…In various patient groups, 10‐20‐30 training conducted as cycling lowered blood pressure and fat mass and increased fat‐free mass and V˙O 2 max, with a high compliance . Furthermore, 10‐20‐30 training decreased blood pressure and lipid profile and increased V˙O 2 max and performance in trained individuals .…”
Section: Introductionmentioning
confidence: 99%
“…An emerging exercise modality is 10‐20‐30 training, consisting of repeated 10‐second sprints followed by 30 and 20 seconds of low and moderate‐intensity exercise, respectively, eliciting a high aerobic and anaerobic load . 10‐20‐30 training elicits an average heart rate (HR) response similar to traditional HIIT (80%–95% of HR peak ) in patients with T2D, and higher than MICT (60%–80% of HR peak ) and SIT (~ 70% of HR peak ) .…”
Section: Introductionmentioning
confidence: 99%
“…Hypertensive individuals demonstrate anomalous muscle mitochondrial turnover and amplified oxidative damage. However, high‐intensity exercise training showed that hypertension‐related impairments can be partly reversed 27 . We need more personalized research on physical activity; however, individualized approaches are often cost‐intensive.…”
mentioning
confidence: 99%